Facilitating EFL students' English grammar learning performance and behaviors: A contextual gaming approach. (July 2020) - Lin, Chi-Jen; Hwang, Gwo-Jen; Fu, Qing-Ke; Cao, Ya-Han
Abstract: The educational value of digital game-based language learning has aroused attention in the English language teaching field. Among all language-specific skills, grammar is seldom addressed in game-based language learning, despite the fact that learning grammar is one of the challenging tasks for English as a Foreign Language (EFL) students. Learners often lack the motivation and enthusiasm to learn and pursue goals for using target grammar in authentic contexts relevant to their lives. The contextual gaming approach could therefore be a potential strategy to provide a springboard for practice and personalization. Thus, to inspire learners and to provide a meaningful English learning context, a contextual game-based learning approach was proposed and presented to an EFL grammar course for first-year college students in a northern Taiwanese university. The treatment was conducted to evaluate the effectiveness and game learning behaviors of the proposed learning approach by situating the experimental group in a contextual game-based learning approach, while the control group learned with a conventional technology-assisted English learning approach. The results revealed that the experimental group's contextual error rate was significantly lower than that of the control group. Analysis of their game learning behaviors further showed differences in the high- and low-achievers' behavior patterns according to Halliday's functions of language development. Some guiding strategies are suggested for low-achievers in future game-based English grammar instruction and research. Highlights: A contextual game-based learning approach was proposed. The experimental group' contextual grammar error rate was significantly decreased. High-achievers usually tried to collect and apply information to resolve problems. Low-achievers usually tended to use surface-layer strategies. Several suggestions for this line of research are proposed.